The Emerging Role of Non-coding RNAs in Drug Resistance of Ovarian Cancer - Lan, Hua; Yuan, Jing; Zeng, Da; Liu, Chu; Guo, Xiaohui; Yong, Jiahui; Zeng, Xiangyang; Xiao, Songshu (Frontiers in Genetics, 2021)
Ovarian cancer is one of the most common gynecological malignancies and has the highest mortality rate among all gynecological malignant tumors. Advanced ovarian cancer patients can obtain a survival benefit from chemotherapy, including platinum drugs and paclitaxel (PTX). In more recent years, the administration of poly-ADP ribose polymerase inhibitor (PARPi) to patients with BRCA mutations has significantly improved the progression-free survival (PFS) of ovarian cancer patients. Nevertheless, primary drug resistance or the acquisition of drug resistance eventually leads to treatment failure and poor outcomes for ovarian cancer patients. The mechanism underlying drug resistance in ovarian cancer is complex and has not been fully elucidated. Interestingly, different noncoding RNAs (ncRNAs), such as microRNAs (miRNAs), long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs), play a critical role in the development of ovarian cancer. Accumulating evidence has indicated that ncRNAs have important regulatory roles in ovarian cancer resistance to chemotherapy reagents and targeted therapy drugs. In this review, we systematically highlight the emerging roles and the regulatory mechanisms by which ncRNAs affect ovarian cancer chemoresistance. Additionally, we suggest that ncRNAs can be considered as potential diagnostic and prognostic biomarkers as well as novel therapeutic targets for ovarian cancer.